PLOTKIN SEMEN YAKOVLEVICH (TO THE 110TH ANNIVERSARY) - S. S. Plotkin; A. V. Dorokhov (Тонкие химические технологии)
The article tells about life and fate of S.Ya. Plotkin, whose 110-th anniversary of birth was marked on March 2016. He was born in 1906 in Melitopole town (Ukraine). Having graduated at the Moscow Institute of Fine Chemical Technology in 1931, he was asked for administration works firstly as the director of the Institute and then as the member of the All-Union Committee for High School problems. During all his life S.Ya. Plotkin successfully combine administrative, scientific, pedagogical and journalistic activities. He was the expert in the problems of hard alloys and powder metallurgy, professor, editor in chief of the journal «History of Natural Sciences and Technique». He was the member of the Journalist’s Union of the USSR, Honorary member of the International Institute for the Sciences of Sintering and Honorary worker of Culture of Russian Federation.